Quantifying Microplastic Leaching from Paper Cups: A Specklegram Image Analytical Approach - Mankuzhy Anilkumar Rithwiq; Puthuparambil Anju Abraham; Mohanachandran Nair Sindhu Swapna; Sankaranarayana Iyer Sankararaman (Photonics, 2024)
The study proposes a novel speckle interferometric method for detecting and quantifying microplastic leaching from paper cups, addressing concerns raised by the World Health Organization regarding human health risks. Hot water at varying temperatures is placed in 36 paper cups from different manufacturers, and the specklegrams of the paper cups’ interior surface are recorded. The quantity of microplastics leached into water is estimated by the Neubauer chamber method, which increases with rising water temperature. Surface morphology analysis through atomic force microscopic images reveals thermal-induced melting and smearing of microplastics, decreasing roughness parameters. Co-occurrence matrix analysis of specklegrams correlates image parameters—inertia moment, homogeneity, energy, contrast, and entropy—with the microplastics count, showing surface modifications and altered pixel intensity distribution with increasing water temperature. Regression equations based on image parameters establish a strong correlation with the microplastics count, that are validated against the Neubauer chamber method. The study indicates contrast as the potential sensitive specklegram feature for microplastics detection and quantification.